German mysticism from Hildegard of Bingen to Ludwig Wittgenstein: a literary and intellectual history - Weeks, Andrew (SUNY series in Western esoteric traditions, 1993)
The union of worlds : biblical and Augustinian sources of German mysticism -- The visible and the invisible : Hildegard of Bingen and female visionary mysticism -- The outer and the inner : the reflective mysticism of Eckhart, Seuse, and Tauler -- The finite and the infinite : the humanistic mysticism of Nicholas of Cusa -- Nature and scripture : mysticism between Renaissance and Reformation -- Letter and spirit : mysticism as dissent in the German Reformation -- The part and the whole : Jacob Boehme and the Baroque synthesis -- Diversity and unity : mysticism between Pietism and Enlightenment -- Nature and imagination : romantic mysticism from Novalis to Schopenhauer